Expression and Roles of Teneurins in Zebrafish - Cheung, Angela; Trevers, Katherine E.; Reyes-Corral, Marta; Antinucci, Paride; Hindges, Robert (Frontiers in Neuroscience, 2019)
The teneurins, also known as Ten-m/Odz, are highly conserved type II transmembrane glycoproteins widely expressed throughout the nervous system. Functioning as dimers, these large cell-surface adhesion proteins play a key role in regulating neurodevelopmental processes such as axon targeting, synaptogenesis and neuronal wiring. Synaptic specificity is driven by molecular interactions, which can occur either in a trans-homophilic manner between teneurins or through a trans-heterophilic interaction across the synaptic cleft between teneurins and other cell-adhesion molecules, such as latrophilins. The significance of teneurins interactions during development is reflected in the widespread expression pattern of the four existing paralogues across interconnected regions of the nervous system, which we demonstrate here via in situ hybridization and the generation of transgenic BAC reporter lines in zebrafish. Focusing on the visual system, we will also highlight the recent developments that have been made in furthering our understanding of teneurin interactions and their functionality, including the instructive role of teneurin-3 in specifying the functional wiring of distinct amacrine and retinal ganglion cells in the vertebrate visual system underlying a particular functionality. Based on the distinct expression pattern of all teneurins in different retinal cells, it is conceivable that the combination of different teneurins is crucial for the generation of discrete visual circuits. Finally, mutations in all four human teneurin genes have been linked to several types of neurodevelopmental disorders. The opportunity therefore arises that findings about the roles of zebrafish teneurins or their orthologues in other species shed light on the molecular mechanisms in the aetiology of such human disorders.